DIGITALISASI LAYANAN AKTA KELAHIRAN SEBAGAI INOVASI PELAYANAN PUBLIK : STUDI INTEROPERABILITAS DATA DISDUKCAPIL DENGAN INSTANSI LAYANAN PUBLIK DI KOTA JAMBI - Thassya Hanifah; Rio Yusri Maulana; Dimas Subekti (STKIP Subang, 2026)
The digitalization of public services represents a strategic effort by governments to realize more efficient, transparent, and citizen-centric service delivery. This study analyzes the digitalization of birth certificate services implemented by the Department of Population and Civil Registration (Disdukcapil) in Jambi City as part of an innovation in public service and examines the level of data interoperability between Disdukcapil and other public service institutions. Using a qualitative case study approach, data were collected through in-depth interviews with users of digital birth certificate services and analysis of official policy documents. The analytical framework refers to the European Interoperability Framework (EIF 2017), which includes four dimensions: legal, organizational, semantic, and technical interoperability. The results show that digitalization enables hospitals to input birth data directly into the Disdukcapil system, reducing administrative burdens and improving service efficiency. Legal and organizational interoperability have been partially implemented, while semantic interoperability is already effective due to data consistency and non-redundant input. However, technical interoperability has not yet reached full integration because users are still required to provide physical documents and perform face-to-face verification. The study concludes that digital birth certificate services in Jambi City have achieved basic interoperability but require cross-sector integration to support the realization of smart and connected public service governance.